1993
DOI: 10.1016/0736-5748(93)90009-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal cholinergic alterations and related behavioral deficits after early exposure to ethanol

Abstract: The present study was designed to ascertain septohippocampal cholinergic alterations and their related behavioral deficits after early exposure to ethanol. Mouse pups were exposed to ethanol, 3 g/kg by daily subcutaneous injection on postnatal days 2-14. At age 50 days, the ethanol-exposed mice had significant reductions from control levels in eight-arm maze performance. For example, on the fourth testing day, the number of correct entries in the ethanol group was 21% below control levels (P < 0.05) and the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Only half of the alcohol-exposed offspring were able to reach criterion, and those that did required significantly more training trials relative to pair-fed controls. Pick et al (1993) reported similar effects in mice injected with ethanol (3 g/kg or 5 g/kg; sc) on PN2-14. At PN50, these mice took twice as many trials as controls to reach criterion, and continued to require significantly more trials than controls to enter all eight arms (Pick et al, 1993).…”
Section: Radial Arm Mazesupporting
confidence: 61%
See 1 more Smart Citation
“…Only half of the alcohol-exposed offspring were able to reach criterion, and those that did required significantly more training trials relative to pair-fed controls. Pick et al (1993) reported similar effects in mice injected with ethanol (3 g/kg or 5 g/kg; sc) on PN2-14. At PN50, these mice took twice as many trials as controls to reach criterion, and continued to require significantly more trials than controls to enter all eight arms (Pick et al, 1993).…”
Section: Radial Arm Mazesupporting
confidence: 61%
“…Pick et al (1993) reported similar effects in mice injected with ethanol (3 g/kg or 5 g/kg; sc) on PN2-14. At PN50, these mice took twice as many trials as controls to reach criterion, and continued to require significantly more trials than controls to enter all eight arms (Pick et al, 1993). Hall et al (1994) showed that midgestational alcohol exposure (i.e., gestational days (GD) 7-13), via 35% EDC liquid diets, was sufficient to impair radial maze acquisition when rats were tested as either juveniles (ϳPN26) or adults (ϳPN80).…”
Section: Radial Arm Mazesupporting
confidence: 61%
“…Alcohol exposure alters cholinergic development and increases AChE and decreases acetylcholine transferase (AChT), diminishing the levels of ACh in cholinergic neurons [197][198][199][200][201]. Cognition is further compromised by the loss of cholinergic neurons [199]. Thus, it is reasonable to think that the expected augmentation of Ach available in the remaining cholinergic neurons, as a conesquence of ChEIs treatment, may improve FASD symptoms.…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…ChEIs block the catabolism of acetylcholine (ACh) by acetylcholinesterase (AChE), which leads to larger pool of available ACh to interact with postsynaptic ACh receptors and induce more lasting effects of this neurotransmitter during postnatal brain development. Alcohol exposure alters cholinergic development and increases AChE and decreases acetylcholine transferase (AChT), diminishing the levels of ACh in cholinergic neurons [197][198][199][200][201]. Cognition is further compromised by the loss of cholinergic neurons [199].…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…Furthermore, DMTP versions of the water maze have shown deficits in rats with hippocampal and dentate gyrus (Steele and Morris, 1999) and fornix/fimbria lesions (Whishaw et al, 1995). Givenr that early postnatal ethanol exposure affects the development of the hippocampus (Bonthius and West, 1990;Greene et al, 1992;Pick et al, 1993), it is reasonable to expect that spatial DMTP-task performance would also be affected by ethanol. This is the first study to use this task to assess the effects of binge ethanol exposure during the brain growth spurt.…”
mentioning
confidence: 97%